2022
DOI: 10.1001/jamanetworkopen.2022.18314
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Handgrip Strength and Dementia Risk, Cognition, and Neuroimaging Outcomes in the UK Biobank Cohort Study

Abstract: IMPORTANCEThe associations between muscle strength and cognitive outcomes have sparked interest in interventions that increase muscle strength for prevention of dementia, but the associations between muscle strength and cognitive aging are unclear, particularly among middleaged adults. OBJECTIVE To evaluate the association between handgrip strength (HGS) and dementia, reduced cognition, and poorer neuroimaging outcomes in a UK population of middle-aged adults. DESIGN, SETTING, AND PARTICIPANTS This cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Previous studies have shown that decreases in gait speed and handgrip strength are correlated with WMHs. 9 , 10 Our study explored the correlation of cerebral WMHs with other indicators of sarcopenia, such as muscle mass and hand grip strength, and cerebral WMHs have also been shown to be associated with cognitive impairment. 11 , 12 Therefore, a series of causal relationships between sarcopenia, WMHs, and cognitive impairment remains to be negotiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that decreases in gait speed and handgrip strength are correlated with WMHs. 9 , 10 Our study explored the correlation of cerebral WMHs with other indicators of sarcopenia, such as muscle mass and hand grip strength, and cerebral WMHs have also been shown to be associated with cognitive impairment. 11 , 12 Therefore, a series of causal relationships between sarcopenia, WMHs, and cognitive impairment remains to be negotiated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that decreased gait speed and handgrip strength are associated with cerebral white matter hyperintensities (WMHs). 9 , 10 A close association between cerebral WMHs and cognitive impairment has been reported in studies that also include meta-analyses. 11–13 The above results suggest that sarcopenia may be mediated through WMHs leading to cognitive impairment.…”
Section: Introductionmentioning
confidence: 88%
“…There is a large body of evidence linking muscular weakness, as determined by low grip strength, to a host of negative ageing‐related health outcomes including diabetes, 1 , 2 physical disability, 3 , 4 , 5 cognitive decline (including Alzheimer's disease 6 ) 7 , 8 and early all‐cause mortality. 9 , 10 , 11 , 12 Given these findings, grip strength has been labelled a ‘biomarker of aging’ 13 ; and yet, this crude metric provides no direct biological plausibility or mechanism linking weakness with chronic disease, physical and cognitive impairments or specific causes of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Another measure of physical function is grip strength as it measures muscular strength and biological validity, and poorer grip strength has been reported to be associated with mortality, and other negative health outcomes [ 17 ]. Recently, some studies [ 14 , 17 19 ] reported that lower grip strength was associated with a higher risk of all-cause dementia. However, from a physiological point of view, walking pace and grip strength may reflect different underlying physiological processes.…”
Section: Introductionmentioning
confidence: 99%